Microstructure, colossal permittivity, and humidity sensitivity of (Na, Nb) co‐doped rutile TiO2 ceramics. Issue 11 (13th May 2019) - Li, Tianyu; Si, Renjun; Wang, Jin; Wang, Shuting; Sun, Jie; Wang, Chunchang
Abstract: (Na0.25 Nb0.75 ) x Ti1− x O2 (NNTO) ceramics ( x  = 0, 0.005, 0.01, 0.02, and 0.05) were prepared by the conventional solid‐state reaction. The microstructure, dielectric, and humidity sensitivity of the ceramics were systematically investigated. Results showed that all ceramics exhibit pure rutile TiO2 phase with dense microstructures. Co‐doping of (Na, Nb) can effectively improve the microstructure homogeneity of the ceramics. When the doping level x  ≥ 0.01, the co‐doped samples show colossal permittivity higher than 10 4 and dielectric loss tangent lower than 0.38. This dielectric behavior features the merit of both frequency and temperature stability in the range of 10 2 ‐10 6  Hz and 100‐300 K, respectively. The co‐doped ceramics were found to be sensitive to the environment moisture. The humidity sensitivity incurs a Maxwell‐Wagner relaxation near room temperature, which further enhances the dielectric permittivity. Excellent humidity sensitive properties of sensitivity to be 102.6 pF/%RH, response/recovery time to be 115/20 seconds, as well as good repeatability, were achieved in the sample with the doping level x  = 0.05. This work underscores that the room temperature dielectric properties of doubly doped TiO2 system depends strongly on the environmental condition and suggests that the (Na + Nb) co‐doped TiO2 ceramics might be promising humidity sensing materials.